Livelihood Sensitivity Matrix: A Novel Technique for Mapping Vulnerability of Rural Households to Climate Change - Usha Das; Souvik Ghosh (Indian Journal of Extension Education, 2018)
Almost all nations are aware of changing climatic scenario and India is not an exception and neither immune from the impact of climate change. The lives of inhabitants are most at risk from cyclone and flood than from drought and heat wave. Poor are the worst affected. Livelihood group wise as well as climatic hazard wise vulnerability index through exposure and impact matrix was developed based on the responses of selected households sampled for present study. To understand the livelihood group wise as well as climatic event wise vulnerability the exposure index and impact index were derived. Crop farmers are most exposed livelihood group followed by labourers, livestock keepers and fish farmers. Cyclone has made highest impact on livelihoods followed by flood, drought and heat wave, respectively. The outlooks for the vulnerable regions are not good unless on-farm contingency plans, both short and long-term, are adopted.